GHAZWUL FIKR AND CAPITALISM SPECTRUM: ISLAMIC STUDENTS ON OLIGARCHY SHADES - Askar Nur (International Conference on Social and Islamic Studies, 2021)
Ghazwul Fikr as a form of attack that emphasizes the basis of human thought becomes a means of perpetuating the power of the capitalist system and also includes the ideology used by oligarchs in controlling power so that no doubt the younger generation, especially Islamic students are often persuaded and faced with a choice, between individual interests and public interests. This study aims to analyze the working mechanism of Ghazwul Fikr as a global political tool in invading the younger generation of Islam and identify oligarchic networks and relations in the lives of Islamic students. This study uses a descriptive method with a literature study approach. The results of this study indicate that Ghazwul Fikr is not only a tool of thought invasion for adherents of Islam but also as a tool to perpetuate the power of capitalism in the economic and political system in Indonesia as well as the involvement of Islamic students in the oligarchic structure.